Primer estudio genético de la nutria marina (Lontra fe L ina ) en la costa peruana - Valqui, Juan (2019)
scats from marine otter (Lontra felina) were collected in august and september 2008 along the species´ distribution at the Peruvian coast. mitochondrial Dna analysis from 24 individuals yielded the first registered sequences of this species, showing relatively high variability (11 haplotypes, h=0.86 and π=0.0117). adaptation of this species to a naturally fragmented habitat could explain why, despite the decreasing population number due to negative effects of human activity at the Peruvian coast in the last decades, the species remains with a relatively high variability. according to predictions of continuous decrease in population numbers and constantly increasing threats due to human activity, further studies deepening the knowledge about genetic structuring of the species´ population and the establishment of at least one protected area at the south of Peru, where regions with high number of individuals have been registered, are recommended.